2005
DOI: 10.1021/jp046141v
|View full text |Cite
|
Sign up to set email alerts
|

Overtone-Induced Decarboxylation:  A Potential Sink for Atmospheric Diacids

Abstract: Atmospheric photochemistry induced by solar excitation of vibrational overtone transitions has recently been demonstrated to be of importance in cleaving weak bonds (in HO(2)NO(2)) and inducing intramolecular rearrangement followed by reaction (in H(2)SO(4)). Here, we propose another potentially important process: the decarboxylation of organic acids. To demonstrate this possibility, we have calculated the decarboxylation pathways for malonic acid and its monohydrate. The barrier to the gas-phase decarboxylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 49 publications
4
76
0
2
Order By: Relevance
“…This reaction is very fast even at low temperatures, making this relevant for chemistry in the tropopause, 100 the midlatitude and polar troposphere, 8,30,33 in volcanic plumes, [101][102][103] and indoors. 8 Catalytic effects of incorporating water into the transition state have been identified in other systems of atmospheric interest, [26][27][28][29] including the reaction of HCl with ClONO 2 to form Cl 2 , which occurs on polar stratospheric clouds. 25 The calculations show that the competing hydrolysis of ON-ONO 2 is not fast enough to significantly suppress the direct channel leading to ClNO formation.…”
Section: Resultsmentioning
confidence: 99%
“…This reaction is very fast even at low temperatures, making this relevant for chemistry in the tropopause, 100 the midlatitude and polar troposphere, 8,30,33 in volcanic plumes, [101][102][103] and indoors. 8 Catalytic effects of incorporating water into the transition state have been identified in other systems of atmospheric interest, [26][27][28][29] including the reaction of HCl with ClONO 2 to form Cl 2 , which occurs on polar stratospheric clouds. 25 The calculations show that the competing hydrolysis of ON-ONO 2 is not fast enough to significantly suppress the direct channel leading to ClNO formation.…”
Section: Resultsmentioning
confidence: 99%
“…complexes at the transition state to decarboxylation. 79 In this example the cyclic transition state complex with water lowers the barrier energy by about 10 kcal mol −1 . Cluster formation opens the possibility of additional low barrier processes, which can be effective in energy dissipation from the initially excited state as illustrated in Figure 3 with the example of the water catalyzed reaction of SO 3 with H 2 O 50, 115-117 and the reverse reaction, dehydration of H 2 SO 4.…”
Section: Bimolecular Reactions In Water Complexesmentioning
confidence: 86%
“…This possibility was suggested based on quantum computations of barrier heights by Staikova and Donaldson for vibrational overtone initiated reactions. 5,79 Nitric and sulfuric acid both form stable complexes with water, which could affect photochemical reaction. [80][81][82][83][84] The transition state energies are lowered in both HNO 3 and H 2 SO 4 by hydrogen bonding to water yet in these clusters the photon energy is dissipated by evaporation.…”
Section: Role Of Water In Sunlight Driven Reactionsmentioning
confidence: 99%
“…OAA is a b-keto acid, and keto carboxylic acid, such as malonic acid, decarboxylate thermally, with activation energies in the range of 20-40 kcal/mol [31,32]. This range of activation energy suggests that relatively low levels of vibrational excitation in the OH stretch mode might induce decarboxylation.…”
Section: Decarboxylation Without Any Catalystsmentioning
confidence: 99%
“…Later the direct decarboxylation of OAA was investigated experimentally by Itob et al [33], and the activation energy was found to be 23.6 kcal/ mol. According to the previous study [32], we have proposed a hydrogen migration mechanism for the direct decarboxylation of OAA. The optimized geometries with selected key geometry parameters are shown in Fig.…”
Section: Decarboxylation Without Any Catalystsmentioning
confidence: 99%